PENGARUH PENGELUARAN PEMERINTAH DAN INVESTASI TERHADAP PERTUMBUHAN EKONOMI DAN TINGKAT KEMISKINAN DI KABUPATEN/KOTA PROVINSI BALI - Suda Pratama, Nengah Rai Narka; Suyana Utama, Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.08.NO.07.TAHUN 2019, 2019)
The economic development of  region is series of activities carried out consciously and continuously to realize  better and more shared situation. Some of factors that cause decline in poverty levels are government spending, investment, economic growth. By looking at the decline in poverty rates in Bali, the researchers want to conduct research on the effects of government spending and investment on economic growth and poverty levels. Data collection through BPS. Path analysis was used. The results of the analysis show that government spending and investment have a positive and significant direct influence on economic growth. Government expenditures have a negative and significant direct influence on poverty levels. Investment has a positive but not significant direct influence on poverty levels and economic growth has a positive and significant direct influence on poverty levels. Government spending and investment do not have an indirect effect on the level of poverty through economic growth.